Evaluation of nonuniform WDM source spacing for EDFA gain characterization - Lear, Kevin L., author; Medberry, John, author; Kulkarni, Shamal, author; IEEE, publisher (Colorado State University. Libraries, 2002)
The accuracy of erbium-doped fiber amplifier gain characterization tests has been evaluated using reduced sets of wavelength-division-multiplexing laser sources. Wavelength grids with both uniform and nonuniform wavelength spacing have been evaluated. Experiments show that it is necessary to maintain equal spectral density of source power per region in order to operate at the same saturation/inversion conditions of the amplifier. By doing so, acceptable results were obtained for a laser configuration with 400-800-GHz nonuniform spacing, employing 12 lasers.
Keywords: optical fiber amplifiers; gain measurement; erbium; optical hole burning; wavelength-division multiplexing